Potential applications of salinity gradient power-heat engines for recovering low-temperature waste heat in cogeneration plants. (1st June 2021) - Catrini, P.; Cipollina, A.; Micale, G.; Piacentino, A.; Tamburini, A.
Highlights: A novel integration of salinity gradient power heat-engines and cogeneration plants is proposed. Energy and economic benefits are evaluated for three case studies in the industrial and tertiary sectors. The integration of a Reverse Electrodialysis heat engine leads to relevant energy and emissions saving. A financial support mechanism is needed for the economic viability of the proposed integration. Coupling these heat engines with heat pumps allows for a size reduction of the cogeneration plant. Abstract: Salinity Gradient Power-Heat Engine is an innovative technology able to convert very low-temperature heat into electricity. Energy and economic benefits could be achieved by integrating this technology into cogeneration plants, where the exploitation of waste heat available during the operation could increase the revenues arising from "High-Efficiency" labels. For the first time, this paper proposes two potential applications in this field, and three illustrative case studies are purposely investigated. In the first case study, a salinity gradient-heat engine converts the waste heat available from a cogeneration plant serving an industrial process. In the second case study, a salinity gradient-heat engine is integrated into a cogeneration plant coupled to a district network. In the third case study, the possibility to reduce the size of a cogeneration plant by coupling this engine with a heat pump is investigated. The analysis relied on simplified models of the integrated systems which were numerically solved. Results for the first case study show an increase of 10.6% in revenues from the high-efficiency support mechanism and electricity selling. In the second case study, the primary energy saving increases from 8.7% up to 10.1%, thus achieving the threshold value for "High-Efficiency" eligibility. In the third case study, the heat engine allows to reduce up to 12.1% the nominal capacity of the prime mover. A prospective analysis of the integration of salinity gradient-heat engine in cogeneration plants is thus presented, and it poses a fundamental reference for future integration of this novel technology into these energy systems.